Social Cohesion Through Cross Cultural Social Interaction in a Multiethnic School: A Study at SMA Negeri 2 Minas, Riau - Rizki Hardi Nata; Wirdanengsih; Erianjoni; Delmira Syafrini; Rosmadi Bin Fauzi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines cross cultural interaction and social cohesion in a multicultural school environment at SMA Negeri 2 Minas, Riau. Cultural diversity in Indonesian schools continues to grow, bringing students from different ethnic backgrounds into shared social spaces. Differences in language, communication styles, and cultural values influence interaction patterns and shape the quality of social relationships among students. The study aims to analyze the dynamics of cross cultural interaction, to explore students’ lived experiences, and to examine the formation of social cohesion in a multietnic school setting. A qualitative approach with a phenomenological design was employed. Data were collected through in depth interviews, observations, and documentation involving students and teachers. Data analysis included data reduction, categorization, and interpretation to identify patterns and meanings. The findings indicate that cross cultural interaction occurs in both formal and informal activities. Students experience acceptance and comfort, as well as challenges such as miscommunication, stereotypes, and group based interaction. Social cohesion develops through shared activities, common interests, and the role of teachers in facilitating interaction, although it is not evenly distributed across all groups. In conclusion, cross cultural interaction shapes students’ social experiences and contributes to the gradual formation of social cohesion through ongoing interaction and adaptation in a multicultural school environment.